Clinical outcomes in cervical cancer patients treated by FDG-PET/CT-based 3-dimensional planning for the first brachytherapy session. Issue 25 (June 2016) - Oh, Dongryul; Huh, Seung Jae; Park, Won; Ju, Sang Gyu; Nam, Heerim; Lee, Jeong Eun
Abstract : Abstract: The aim of the study was to evaluate the treatment outcomes in cervical cancer patients treated with 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/computed tomography (CT)-guided 3-dimensional brachytherapy (3D-BT) planning for the first brachytherapy session. We retrospectively analyzed 87 patients with cervical cancer who received definitive radiotherapy (RT). Primary tumor size was ⩽4 cm in 22 patients (25.3%), >4 cm and ⩽6 cm in 45 patients (51.7%), and >6 cm in 20 patients (23.0%). The median total dose of external beam RT was 50.4 (50.4–60.4) Gy. FDG-PET/CT-guided 3D-BT with an iridium-192 source was performed. The clinical target volume (CTV) for 3D-BT included the entire cervix and the abnormal FDG-uptake with a 1-cm expansion. A planned total dose was 24 Gy at 4 Gy per insertion 3 times per week using a tandem and 2 ovoids. The mean D95 and D90 for the CTV were 73.4 (±5.9) Gy and 77.9 (±6.9) Gy, respectively (EQD2, α/β=10). The D2cc for the rectum and bladder was 374 (±97.4) cGy and 394 (±107.6) cGy per fraction, respectively. The EQD2 (α/β=3) for the D2cc was 74.5 (±12.4) Gy for the rectum and 77.3 (±14.6) Gy for the bladder. The median follow-up period was 40 (8–61) months. The 3-year overall survival (OS), progression-free survival (PFS), and local control (LC) rates were 84.7%, 72.1%, and 89.2%, respectively. The 3-year LC rate was 100% for tumors ⩽ 4 cm, 91.1% for tumors > 4 cm and ⩽ 6 cm, and 70.5% for tumors > 6 cm ( P  = 0.014). Local failure developed in 9 patients. Three patients had local failures outside of the CTV. Grade 1, 2, and 3 rectal bleeding developed in 5, 4, and 2 patients, respectively. One patient experienced rectovaginal fistula. FDG-PET/CT-guided 3D-BT planning is a feasible approach, which showed favorable clinical outcomes.